The Effects of International Financial Reporting Standard Adoption on Conservatism in Malaysian Banks - Wan Abdullah, Wan Rabia’tul A’dawiyah; Marzuki, Marziana Madah (Asian Journal of Empirical Research, 2021)
The purpose of this study is to investigate the effect of IFRS full convergence in 2012 on conservatism of banks in Malaysia. Based on 66 firm-year observations of Malaysian banks listed in the main market of Bursa Malaysia, the results of this study reveal an overall increase in conservatism during the study period and a higher increase of conservatism following IFRS adoption. The results also provide evidence of significant differences in the level of conservatism in pre- and post-adoption of IFRS. The findings of this study highlight the benefit of IFRS full convergence among the banks in Malaysia in enhancing financial reporting quality proxied by conservatism. Thus, this study provide implication to the regulators and banks to continually support IFRS adoption as the standard continually change over the time. Our result also provides new evidence on the effect of IFRS on conservatism for financial sector which have different regulatory framework from other sectors.